Laa hasil - Umaira ahmed (Ferozesons; Lahore, 2000)
"Laa Hasil" by Umera Ahmed is a deeply introspective novel that explores the complexities of unfulfilled desires, spiritual struggle, and the quest for meaning in a world full of distractions and illusions.